2003
DOI: 10.1053/rmed.2002.1459
|View full text |Cite
|
Sign up to set email alerts
|

Breathing frequency and use of expiratory muscles do influence the dynamic positive end-expiratory pressure

Abstract: End-expiratory air trapping due to obstructive airway disease can be estimated through the measurement of intrinsic positive end-expiratory pressure PEEPi. The influence of breathing-frequency and use of expiratory muscles on PEEPi were measured in 10 normal and 10 chronic bronchitic patients (COPD). Insignificant control values of PEEPi increased to measurable values at high breathing rate in normal subjects. Control values were higher in COPD patients and increased at fast breathing rate. When corrected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
10
2
Order By: Relevance
“…Second, mean respiratory rate during the 6 mL/kg strategy was 34 breaths/min, considerably higher than the mean respiratory rates of the subjects in the 6 mL/kg group of both the ARDS Network study and our subgroup. Our work and previous studies have demonstrated an association between respiratory rate and intrinsic PEEP (15,19). Finally, the timing of intrinsic PEEP measurements differed between these studies.…”
Section: Discussioncontrasting
confidence: 54%
“…Second, mean respiratory rate during the 6 mL/kg strategy was 34 breaths/min, considerably higher than the mean respiratory rates of the subjects in the 6 mL/kg group of both the ARDS Network study and our subgroup. Our work and previous studies have demonstrated an association between respiratory rate and intrinsic PEEP (15,19). Finally, the timing of intrinsic PEEP measurements differed between these studies.…”
Section: Discussioncontrasting
confidence: 54%
“…6,25,26 In chronic conditions such as congestive heart failure, slowing respiratory rate as practiced in yoga has shown to reduce the sensation of dyspnea and improve exercise performance, 24 whereas studies in patients with COPD have shown increased respiratory muscle recruitment with pursed lip breathing, which again is a component of pranayama, 27 relief of dyspnea and increased leg effort after lower extremity exercise training, 28 and reduction in dynamic hyperinflation with lower respiratory rates as achieved in yoga. 29,30 Potential limitations of our study merit consideration. First, the QOL was assessed on a short-term basis.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, we did not measure expiratory muscle activity, which has been shown to occur with the application of CPAP during exercise (4,10). Furthermore, we did not measure actual PEEPi.…”
Section: Discussionmentioning
confidence: 88%
“…If a patient did not have PEEPi, the application of CPAP and CNP would ordinarily cause hyperinflation (11)(12)(13). The decrease in respiratory rate that occurred with CNP could also have resulted in a decreased PEEPi (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation